PENGARUH TANGIBILITY, GROWTH OPPORTUNITY, DAN UMUR PERUSAHAAN TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Barang dan Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Febriani, Nur Leni Budi; Suprihati, Suprihati; Rukmini, Rukmini (ITB AAS INDONESIA, 2024)
This research aims to analyze the influence of tangibility, growth opportunity, and company age on company performance in sub-goods and consumer manufacturing companies listed on the Indonesia Stock Exchange 2018-2022. The sampling technique in this research used the purposive sampling method. The research method used is quantitative research with a sample size of 14 consumer goods and consumption companies listed on the Indonesia Stock Exchange. The analysis used is path analysis using SPSS version 23. The research results show that growth opportunity and company age influence company performance. Meanwhile, tangibility has no effect on company performance.